Pokémon : The Chikorita Challenge [anglicky] / Book 14 - West, Tracey, 1965- (Orchard Books, 2021)
When Ash and Pikachu befriend a new Grass-type pokémon, they can´t wait to welcome it to the team. But trickstersTeam Rocket are hatching a plan to lure the Chikorita away, stealing it for themselves.